Crimes unspoken: the rape of German women at the end of the Second World War - Gebhardt, Miriam (Polity, 2017)
Seventy years too late -- Wrong victims? -- How many were affected -- Sexual aggression against men -- A word about method -- Berlin and the east - chronicle of a calamity foretold -- The great fear -- The Red Army comes -- Berlin -- Year on -- Extracts from police reports -- A different perspective -- South Germany - who will protect us from the Americans? -- No one's time -- Moderate indignation -- A "feeling of great insecurity among our soldiers" -- Discussion -- A "sexual conquest of Europe"? -- Unbroken assertion of power by the occupiers -- Parallels and differences -- Pregnant, sick, ostracized - approaches to the victims -- Victims twice over -- Fraternization -- The abortion problem -- No one's children -- "The other victims are also taken care of" -- First the French, then the public authorities -- "I love this child as much as the others" -- The long shadow -- The effects of the experience of violence -- The myth of female invulnerability -- "Anonymous" and the censorship of memory -- Duties of loyalty -- First feminist protests -- Helke Sander's "BeFreier" and the German victim debate -- The past today